Tool Path Generation for Free form Surfaces Using B-Spline Surface - Randhawa, Simranpreet Singh (My University, 2012)
Tool path generation is an important step for the machining of the free form surfaces. The accuracy of machining free form surfaces greatly depends upon the tool path. A number of algorithms had been proposed by different researchers for the accurate and efficient tool path generation for the machining of the free form surfaces.The present study is focused on implementation of an algorithm given by Choi and Banerjee[29]that generates tool paths for free-form surfaces based on the accuracy of a desired manufactured part. This algorithm includes two components. First is the forward-step function that determines the maximum distance between two cutter contact points with a given tolerance. The second component is the side step function which determines the maximum distance between two adjacent tool paths with a given scallop height. These functions are independent of the surface type and are applicable to allcontinuous parametric surfaces that are twice differentiable. This algorithm reduces Cutter Contact points while keeping the given tolerance and scallop height in the tool paths. The algorithm is thereafter modified using the B-spline surface. The modified algorithm is then used to machine a wax component which is compared with the desired surface.
M.E. (CAD/CAM and Robotics)
Keywords: Free Form Surfaces; B-Spline Surface; CNC Machine